On the Analysis of Extended Partial Metric Space Combined withFuzzy Soft Structure - Mohsen, Salim Dawood; Ramk, Hawraa Godarz (Iraqi Journal of Science, 2026)
This note introduces a new extended concept into a fuzzy soft area that plays a prominent role in functional analysis, called the fuzzy soft b-partial metric space, which is an extension of the fuzzy soft metric space and the fuzzy soft partial metric space. The research discusses numerous analytical features based on this proposed space, including the -closed, -open ball, -Hausdorff space, and -converge sequence. Moreover, several essential theorems of convergence of this space are investigated. Furthermore, close connections between this newly defined space and b-metric spaces are also examined. In this regard, several instances are illustrated.